2021
DOI: 10.1177/00472875211046052
|View full text |Cite
|
Sign up to set email alerts
|

No Story Without a Storyteller: The Impact of the Storyteller as a Narrative Element in Online Destination Marketing

Abstract: Storytelling constitutes a promising tool in destination brand communication. Yet, although it also emerged as an important research field, studies on how individual story elements impact story persuasiveness are scant. This study investigates the impact of the storyteller as a narrative element (third person vs. first person) on tourist response. Findings show that first-person compared to third-person storytellers significantly increase engagement on social media, destination brand image, and tourist visit i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(16 citation statements)
references
References 97 publications
0
16
0
Order By: Relevance
“…Previous studies on the perceived influences of SMMAs have mostly appeared in literature on luxury brands (Godey et al 2016; Kim and Ko 2012; Liu, Shin, and Burns 2021; Zollo et al 2020), with little in the airline industry (Seo and Park 2018) and e-commerce (Yadav and Rahman 2017); the current study provides a comprehensive foundation that extends the theoretical interpretation of SMMAs to the tourism context. Furthermore, relevant studies in the field have mainly been conducted on social media platforms, such as the role of social media in marketing (Pachucki, Grohs, and Scholl-Grissemann 2021) and the use of social media by tourists (Amaro, Duarte, and Henriques 2016). This study applied the SMMA model proposed by Kim and Ko (2012) to tourism for the first time and reflects an important new direction for the study of social media marketing in the field.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on the perceived influences of SMMAs have mostly appeared in literature on luxury brands (Godey et al 2016; Kim and Ko 2012; Liu, Shin, and Burns 2021; Zollo et al 2020), with little in the airline industry (Seo and Park 2018) and e-commerce (Yadav and Rahman 2017); the current study provides a comprehensive foundation that extends the theoretical interpretation of SMMAs to the tourism context. Furthermore, relevant studies in the field have mainly been conducted on social media platforms, such as the role of social media in marketing (Pachucki, Grohs, and Scholl-Grissemann 2021) and the use of social media by tourists (Amaro, Duarte, and Henriques 2016). This study applied the SMMA model proposed by Kim and Ko (2012) to tourism for the first time and reflects an important new direction for the study of social media marketing in the field.…”
Section: Discussionmentioning
confidence: 99%
“…Although social media has been extensively discussed in academic studies (e.g., Önder, Gunter, and Gindl 2020; Pachucki, Grohs, and Scholl-Grissemann 2021; Uşaklı, Koç, and Sönmez 2017), the field of SMMAs is still in its infancy and has been primarily studied in branding literature (e.g., Liu, Shin, and Burns 2021; Seo and Park 2018; Zollo et al 2020). While a handful of studies have explored SMMAs in the context of tourism (Lee et al 2021; Leung, Bai, and Stahura 2015; Leung, Bai, and Erdem 2017), their effectiveness in destination marketing remains under-studied (Shao et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Perceived social presence can indicate credibility for consumers, influencing their intention to visit a destination. Using the test results, Pachucki et al [90] concluded that social presence impacted the intention to visit. Eighth, the results of the hypothesis testing show that social presence (H8) has a significant impact on consumer e-WOM.…”
Section: Discussionmentioning
confidence: 99%
“…This provides a comprehensive portrayal of a sense of life or presence concerning the destinations [89]. As a result of the perceived social presence, consumers perceive credibility, influencing their intention to visit destinations [90]. Additionally, social presence positively impacts the development of trust in a social environment [91].…”
Section: Customer Engagement and Outcome Behavior Ofmentioning
confidence: 99%
“…Their users, who are perceived as storytellers, may influence perception and buying behaviour of other people, and can co-create brands, including tourism destination brands (Lund, Cohen and Scarles, 2018). These storytellers significantly increase engagement of other social media users, destination brand image and visits intentions (Pachucki, Grohs and Scholl-Grissemann, 2021). On the other hand, social media users and their posts can as well harm and co-destruct destinations´ reputation (Lund, Scarles and Cohen, 2019).…”
Section: Introductionmentioning
confidence: 99%